Design of high selectivity narrowband eight-order high-temperature superconducting sextaplexer. (12th October 2020) - Wang, Li-Tian; He, Ming; Xiong, Yang; Zhang, Wei; Chen, Hai-Hua; Ji, Lu
Abstract: A C-band high-temperature superconducting six-channel multiplexer (sextaplexer) is proposed in this paper. A distributed coupling scheme is introduced, with which the bandpass filter (BPF) in each channel can be designed individually. The computational complexity of the proposed method is linearly increased as the number of the channels is getting larger, which is much lower than the traditional method. The proposed coupling scheme requires no extra matching network, which helps to reduce the size of the multiplexer circuit. The sextaplexer consists of six high-order BPFs with cascaded quadruplet structure. A pair of transmission zeros can be introduced to make the BPF have high selectivity. The example sextaplexer works at the C-band and each fractional bandwidth is about 0.8%. The center frequency ratios and the isolations of each adjacent channel can reach 1.01 and 42 dB, respectively. The measurement results match well with the simulation results, which verifies the effectiveness of the proposed method.